2021
DOI: 10.1088/1755-1315/796/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Deterioration Analysis for Rural Roads using HDM-4

Abstract: Highway Development and Management (HDM-4) is comprised of decision-making tools used to assess the economic, social, and environmental viability of project development proposals to arrive at the best investment decisions. The entire system is built on various functions of pavement performing under numerous structural and environmental influences. The present work aims to study pavement distress and deteriorations prevailing on rural roads. At each stage, the road deterioration models predict impacts of distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The root mean square error (RMSE) and absolute error (AAE) are used to develop the calibration factors. [4] The study demonstrated that future pavement performance can be predicted using curve distress and the expansion of traffic consideration. In light of financial considerations, it is essential information for alternative pavement maintenance strategies.…”
mentioning
confidence: 88%
“…The root mean square error (RMSE) and absolute error (AAE) are used to develop the calibration factors. [4] The study demonstrated that future pavement performance can be predicted using curve distress and the expansion of traffic consideration. In light of financial considerations, it is essential information for alternative pavement maintenance strategies.…”
mentioning
confidence: 88%